Methods for diagnosing perceived age on the basis of an ensemble of phenotypic features - Coma M; Valls R; Mas JM; Pujol A; Herranz MA; Alonso V; Naval J (Dove Medical Press, 2014)
Mireia Coma,1 Raquel Valls,1 José Manuel Mas,1 Albert Pujol,1 Miquel Angel Herranz,2 Vicente Alonso,2,3 Jordi Naval21Anaxomics Biotech, Barcelona, Spain; 2Genocosmetics Laboratory, Barcelona, Spain; 3Unidad de Dermatología del Hospital Nisa 9 Octubre de Valencia, Valencia, SpainBackground: Perceived age has been defined as the age that a person is visually estimated to be on the basis of physical appearance. In a society where a youthful appearance are an object of desire for consumers, and a source of commercial profit for cosmetic companies, this concept has a prominent role. In addition, perceived age is also an indicator of overall health status in elderly people, since old-looking people tend to show higher rates of morbidity and mortality. However, there is a lack of objective methods for quantifying perceived age.Methods: In order to satisfy the need of objective approaches for estimating perceived age, a novel algorithm was created. The novel algorithm uses supervised mathematical learning techniques and error retropropagation for the creation of an artificial neural network able to learn biophysical and clinically assessed parameters of subjects. The algorithm provides a consistent estimation of an individual's perceived age, taking into account a defined set of facial skin phenotypic traits, such as wrinkles and roughness, number of wrinkles, depth of wrinkles, and pigmentation. A nonintervention, epidemiological cross-sectional study of cases and controls was conducted in 120 female volunteers for the diagnosis of perceived age using this novel algorithm. Data collection was performed by clinical assessment of an expert panel and biophysical assessment using the ANTERA 3D® device.Results and discussion: Employing phenotype data as variables and expert assignments as objective data, the algorithm was found to correctly classify the samples with an accuracy of 92.04%. Therefore, we have developed a method for determining the perceived age of a subject in a standardized, consistent manner. Further application of this algorithm is thus a promising approach for the testing and validation of cosmetic treatments and aesthetic surgery, and it also could be used as a screening method for general health status in the population.Keywords: perceived age, algorithm, dermatology, diagnostic method, skin aging